Description Of The Level Of Public Knowledge About Gastritis In Pangombusan Village Parmaksian District - Ferawati Ginting; Hepni Hepni; Heny Kurniasari; Renti Silaban (CV. AFDIFAL MAJU BERKAH, 2026)
Gastritis is an inflammation of the gastric mucosa that can be triggered by various factors, including Helicobacter pylori infection, the use of nonsteroidal anti-inflammatory drugs (NSAIDs), irregular diet, stress, and alcohol consumption. Public knowledge about gastritis plays a role in prevention and early treatment efforts to prevent more serious complications. This study used a quantitative descriptive study using a purposive sampling technique. A total of 87 respondents were included as the study sample. The results of the study showed that most of the people in Sosor Sihobuk Hamlet, Pangombusan Village, had a good level of knowledge about gastritis. Based on the research results, it is recommended that the public maintain and improve their knowledge about gastritis through active participation in health education activities, seeking information from reliable sources, and adopting a healthy lifestyle, such as eating regularly and avoiding factors that trigger gastritis.